Namesakes: The Experience of Sharing One's Full Name with a Celebrity. (3rd April 2017) - Ephratt, Michal
Abstract : The study investigates the relationships, attitudes, and emotions about oneself, one's identity, singularity, and relatedness as they emerge from qualitative, in-depth interviews with Israelis who happen to share the same given name and surname of famous Israelis. Analyzing their experiences resulted in three core themes organized along two axes: a substantive axis covering identity and namesake and an instrumental axis related to non-typical functions of the name as well as intersubjective management and onomastic strategies. These two axes, highlighted through namesakes, intersect in the real-life experiences of the interviewees, helping to inform a theory of personal names.